A study on infectious disease propagation in an airport network - Tee, Poh San (2015)
In this study, simulations based on several values of three parameters were done to show the Ebola disease propagation. A modified SEIR model was used to demonstrate the relationships between each variable of an infectious disease in transmission and how it affects the dynamics of transmission in different geographic locations. Global air travel data was obtained to form a complex air traffic network to assist in this simulation. Discoveries showed that Singapore has chances in exposing to Ebola disease even though the odd is very small. Different transmission variables portray different results and duration in disease propagation. Personal insights were discussed to provide a different view in perspective.